Four Sistine Ethiopians? The 1481 Ethiopian Embassy and the Frescoes of the Sistine Chapel in the Vatican - Bonechi, Marco (Aethiopica, 2011)
As proposed by several scholars, among the many modern on-lookers depicted on the walls of the Sistine Chapel in the Vatican, foreign diplomats are also portrayed: e.g., the Portuguese ambassador and the Florentine emissaries. In the present paper it is suggested that portraits of four of the six members of the momentous Ethiopian delegation – which was headed by Antonio, chaplain of aṣe Ǝskǝndǝr, and arrived at Rome in the first half of November 1481 – may be identified in two scenes, i.e. the Temptation of Moses by Sandro Botticelli and the Crossing of the Red Sea by Biagio d’Antonio Tucci. The paper focuses on the relationship between the visual representation of these four men – Antonio being most probably included – and two contemporary literary works: the treatise by Paride de Grassi on the ambassadors to the Roman curia and the writing by Andreas Trapezuntius on the Roman political situation at the end of 1481 respectively. Such topics as the genuflexion of the Ethiopians and the content of Sixtus IV with the Ethiopian embassy are dealt with. The importance of the suggested identifications for the problematic chronology of the frescoes is also discussed, and so a few other aspects of the two narrative scenes.